Game Simulation pada Pembelajaran Ekonomi di Sekolah Menengah Atas - Mutiya Oktariani; Ahmad Supendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of the Virtonomics simulation game method on the understanding of the concept of modern economic problems in grade X.IPS students. This study uses a quasi-experimental design with pretest-posttest nonequivalent control group design. The participants in this study were 30 grade X.IPS students at a high school in Merauke. The results of the study showed that there was a difference in test results between the pre-test and post-test obtained by students in the experimental class who used the simulation game method. The conclusion is that there is a difference in test results between the pre-test and post-test obtained by students in the experimental class who used the simulation game method.